Crime of Fraud in Vacancy of Freelance Job under the Guise of Like and Follow on Social Media - Ayudhianti Pranchastika; Chazizah Gusnita (Dinasti Publisher, 2024)
Social media as a means of communication and information exchange can now be utilized to create new jobs. However, the development of information and communication technology in the use of social media also has a negative impact, there is a group of people who are less responsible for its use, causing someone to suffer physical, psychological, and financial losses. The fraud of freelance under the guise of like and follow is a clear example of the negative impact that is present. This research uses an analytical descriptive qualitative approach with data collection through observation, interviews, and literature review to obtain clear and in-depth information about the role and typology of victim vulnerability in this fraud case. The results show that vulnerability factors such as youth, women, parents, narrow-minded people, depressed people, and greedy people support victimization. Thus, there is a need for prevention that can be started by oneself, the community, and law enforcement officials in educating and analyzing incoming fraud case reports, thus preventing the increasing number of victims.